2016
DOI: 10.1038/srep22524
|View full text |Cite
|
Sign up to set email alerts
|

In-situ Quasi-Instantaneous e-beam Driven Catalyst-Free Formation Of Crystalline Aluminum Borate Nanowires

Abstract: The catalyst-assisted nucleation and growth mechanisms for many kinds of nanowires and nanotubes are pretty well understood. At times, though, 1D nanostructures form without a catalyst and the argued growth modes have inconsistencies. One such example is the catalyst-free growth of aluminium borate nanowires. Here we develop an in-situ catalyst-free room temperature growth route for aluminium nanowires using the electron beam in a transmission electron microscope. We provide strong experimental evidence that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…50,51 Gonzalez-Martinez et al performed a similar experiment to that of Sood et al but irradiating precursors that did not contained tunsgten. 119 In this case the precursors were composed by round amorphous micron-sized particles containing Al, B and O. The precursors quasi-instantaneously transformed into bundles of Al 5 BO 9 NWs sticking out from an amorphous scaffold remnant from the original precursors, a structure that resembles a sea urchin (see Fig.…”
Section: Catalyst-free Beam-induced Synthesis Of Quasi-one Dimensiona...mentioning
confidence: 99%
“…50,51 Gonzalez-Martinez et al performed a similar experiment to that of Sood et al but irradiating precursors that did not contained tunsgten. 119 In this case the precursors were composed by round amorphous micron-sized particles containing Al, B and O. The precursors quasi-instantaneously transformed into bundles of Al 5 BO 9 NWs sticking out from an amorphous scaffold remnant from the original precursors, a structure that resembles a sea urchin (see Fig.…”
Section: Catalyst-free Beam-induced Synthesis Of Quasi-one Dimensiona...mentioning
confidence: 99%
“…The catalogue of nanostructures synthesized inside the TEM without the need of especially customized holders has expanded greatly [1] since the first reported production of Au nanoparticles over 23 years ago [2]. Up to date, nanostructures of all three dimensionalities have been produced inside the TEM, among which we have zero-dimensional (0D) of pure metals [2][3][4][5][6][7][8][9][10], metallic alloys [11,12] and metal oxides [13]; one-dimensional (1D) nanowires made of Ag [14,15], Cu [16,17], Te [18], Cu-Ag [19], Al 5 BO 9 [20], B/BO X [21], WO X [22][23][24] and SiO 2 [25] nanorods; and finally, two-dimensional (2D) Fe [26], ZnO [27], CuO [28] and Cr [29] membranes and free-standing graphene flakes have also been obtained [30]. Still, this catalogue pales in comparison to that of the nanostructures manufactured by more conventional techniques such as chemical vapor deposition (CVD) [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Except for the Fe, ZnO, CuO and Cr membranes [26][27][28][29] all the nanostructures listed above were produced following essentially the same protocol in the TEM. The method consists of making the microscope's e-beam converge gradually over a micron-sized precursor particle supported on the C substrate of the TEM grid (we have described this method in more detail elsewhere) [20,21,30]. What generally occurs is that the precursor particle begins to disintegrate after a certain current density threshold J T is reached by making the beam gradually converge upon it (this generic protocol can be labeled as 'convergent beam protocol' or CBP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, radiation damage of electron beam is undesirable, however, recent experiments have demonstrated that it can have beneficial effects 6 , 7 , 9 12 . Examples are precise cutting of single-walled carbon nanotubes using electron beam 13 , electron-beam-assisted coalescence or joining of single-walled carbon nanotubes 14 16 and metallic nanowires 17 , interesting phenomena due to electron beam irradiation such as phase transformation in graphite 18 , 19 , α-FeSi 2 20 , and Sn-based nanowires 21 , controlled growth-reversal of catalytic carbon nanotubes 22 , and extreme pressure inside carbon nanotubes 23 , 24 , electron-beam-induced formation of nanostructures like carbon onions 25 , double-walled nanotubes 26 , nanopores 27 , alumina nanocapsules 28 , silicon nanocrystals 29 , 30 , and crystalline aluminum borate nanowires 31 , restructuring of NaREF 4 nanocrystals under electron beam irradiation 32 , just to mention a few. In these examples, the applied electron energies are all equal to or greater than 200 keV and even up to MeV, which makes possible the atomic displacement.…”
Section: Introductionmentioning
confidence: 99%